Avaliação Táctica no Voleibol: O posicionamento defensivo e zonas vulneráveis em função da zona do ataque adversário no 5º jogo da fase final do Play-Off Divisão A1 - Francisco Gonçalves; Paulo Mourão (Desafio Singular, 2008)
To hit the Volleyball game's objective, the players must perform individual actions that in a specific structure form the tactic thought. Thus, it is important to verify the game's actions, in this case the defensive tactic thought to find the best form to oppose it. The present study, intends to analyze the defensive tactic organization, as well as the place of touch of the ball in the ground, in function of the attack zone, trying to find a vulnerable zones standard. The offensive actions that had originated direct point, of the teams presents in 5º game of the end of the Play-Off, of the championship of masculine senior of Volleyball (Sport Lisboa e Benfica and Sporting Club de Espinho), had been analyzed. The defensive positioning of the team was analyzed, as well as the place of touch of the ball, dividing the field in 9 possible defensive zones. We concluded that the Benfica's defensive zones most vulnerable are the areas next to the line of the 3 meters. In turn, the Espinho presents vulnerability in the centre and the left, behind the line of the 3 meters. The relevancy of this quantitative tactic analysis, allows to determine as the offensive tactic structure will have to be plan by the adversaries teams, with intention to explore these vulnerable zones.